PENDAPAT SISWA TENTANG FUNGSI KEGIATAN EKSTRAKURIKULER DI SMP N 22 PADANG - Putra, Febi Bayu; Ilyas, Asmidir .; ., nurfarhanah . (Universitas Negeri Padang, 2013)
Â Abstract: Extracurricular activity is another activity that is done in extra time. That has purpose to get more knowledge and skill of students. In fact there are some of students did not know extracurricular activity because of some reason.This research is descriptive research. The population of research is students of class VIII SMPN 22 Padang, a number of 298 populations. The sample takes as random with random sampling75 populations. The data is collected by using enquette. Analyzed by using percentage technique. The research said 1). The talent thatâ€™s had by students channeled well after following extracurricular activity. 2). After following extracurricular activity, the students can develop their social ability in society. 3). Students creativity can channel well after following extracurricular activity at SMPN 22 Padang. 4). After following extracurricular activity at SMPN 22 Padang, students can make a plan student career in future based on the research, we hope that headmaster gives support to extracurricular activity with delivering facility as student needed, giving a facilitator with hoping the achievement of students will expand as optimal. Beside that it can continue of extracurricular as optimal. Keyword: activity extracurricular expeand knowledge s students Â